EFFECTS OF WEARING AN ANKLE BRACE ON GROUND REACTION FORCES DURING JUMPS IN BASKETBALL GAME SIMULATION - Castro,Alex (2021)
ABSTRACT Introduction: The use of ankle braces reduces the risk of ankle injuries in basketball players. However, the mechanisms of injury protection provided by the ankle braces in the basketball game are still unknown. Objectives: To analyze the effects of wearing a lace-up ankle brace, and to conduct an exercise protocol that simulated the intensity of the basketball game on ground reaction force (GRF) during basketball-specific vertical jumps. Methods: Eleven male younger basketball players aged under 18 completed 48 vertical jumps, with and without ankle braces, during an exercise protocol composed of four 10-minute periods, simulating the activity profile and intensity of the basketball game as well as the typical intervals between periods. Mediolateral (variables: the greatest medial and lateral peaks) and vertical (variables: vertical peak, impulse peak, impulse at 50 ms of landing, loading rate and jump height) GRF were measured during takeoff and landing for all the jumps performed in the exercise protocol. Results: The use of the ankle brace reduced mediolateral GRF in all periods of the exercise protocol during takeoff and landing ( P < 0.05), without affecting the vertical GRF ( P > 0.05). Mediolateral and vertical GRF (takeoff mediolateral vertical peaks, landing mediolateral peaks, landing impulse peak, takeoff and landing loading rate) increased significantly during four subsequent 10-minute periods ( P < 0.05). However, for mediolateral GRF, the increase overtime was higher without braces. Conclusions: The use of the ankle brace reduced the mediolateral GRF on the lower limb, while there was a progressive increase in the external load applied to the body during the vertical jumps in the subsequent periods of the exercise protocol performed at the same intensity of the basketball game. Level of evidence I; Randomized clinical trial .